Sharia Capital Market Education and Investment Accessibility: Determinants of Students’ Investment Intentions - Luthfia Masfa Nur; Juliana Nasution; Nur Ahmadi Bi Rahmani (Jurnal Investasi Islam, 2026)
This study examines the effect of sharia capital market education and investment accessibility on students’ investment intentions. While prior studies have predominantly focused on financial literacy and general investment intention, limited research integrates structured educational interventions with accessibility factors within the sharia investment context. This study adopts a quantitative approach using primary data collected from students at Universitas Islam Negeri Sumatera Utara. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results indicate that participation in sharia capital market education significantly influences investment intention (t = 10.266; p < 0.001). Investment accessibility, represented by the ease of account opening, also shows a significant positive effect (t = 3.525; p < 0.001). The model explains 89.2% of the variance in investment intention (R² = 0.892). This study contributes to the literature by integrating educational intervention and accessibility within the framework of the Theory of Planned Behavior and behavioral finance. The findings highlight that structured education combined with accessible investment platforms plays a critical role in shaping students’ intention to invest in sharia financial instruments.